Validation of R-hf risk score for risk stratification in ischemic heart failure patients: A prospective cohort study. (August 2022) - Rajan, Rajesh; Soman, Suman Omana; Al Jarallah, Mohammed; Kobalava, Zhanna; Dashti, Raja; Al Zakwani, Ibrahim; Al Balool, Joud; Tse, Gary; Setiya, Parul; Brady, Peter A.; Al-Saber, Ahmad; Vijayaraghavan, Govindan
Abstract: Background: The aim of this study was to validate R-heart failure (R-hf) risk score in ischemic heart failure patients. Methods: We prospectively recruited a cohort of 179 ischemic and 107 non-ischemic heart failure patients. This study mainly focused on ischemic heart failure patients. Non-ischemic heart failure patients were included for the purpose of validation of the risk score in various heart failure groups. Patients were stratified in high risk, moderate risk and low risk groups according to R-hf risk score. Results: A total of 179 participants with ischemic heart failure were included. Based on R-hf risk score, 82 had high risk, 50 had moderate risk and 47 had low risk heart failure scores. More than half of the patients having R-hf score of <5 had renal failure (n = 91, 50.8%) and anemia (n = 99, 55.3%). Notably, HFrEF was more prevalent in patients with high risk score (74, 90.2%). Patients with high risk score had significantly higher creatinine (2.63 ± 1.96, p < 0.001), Troponin-T HS (59.9 ± 38.0, p < 0.001) and PRO BNP (17842 ± 6684, p < 0.001) when compared to patients with low and moderate risk score. Patients with low risk score had significantly higher Hb (13.2 ± 1.85, p < 0.001), Albumin (3.69 ± 0.42, p < 0.001) and GFR (90.0 ± 8.04, p < 0.001). A R-hf score of <5 was a significant predictor of mortality in ischemic (OR = 50.34; 95% CI [16.94–194.00, p < 0.001) and non-ischemic (OR = 46.34; 95% CI [12.97–225.39], p < 0.001) heart failure patients. Conclusions: Lower R-hf risk score is a significant predictor of mortality in ischemic and non-ischemic heart failure patients. Risk score can be accessed at https://www.hfriskcalc.in . Highlights: R-hf risk score is a robust tool (a derivative of e-GFR, EF, Hb, and NT proBNP) to predict heart failure mortality. Lower R-hf risk score is a significant predictor of mortality. Rajan's-hf risk score calculator will be available at https://www.hfriskcalc.in/ .